2018
DOI: 10.1080/01635581.2018.1464347
|View full text |Cite
|
Sign up to set email alerts
|

Latest in Vitro and in Vivo Assay, Clinical Trials and Patents in Cancer Treatment using Curcumin: A Literature Review

Abstract: Curcumin, the main active compound of the curcuma root, shows antioxidant, anti-inflammatory, and antitumor properties which have been demonstrated in preclinical and clinical trials. Its antitumor activity is mediated by its ability to act directly on the tumor cell, activating apoptosis pathways and indirectly inhibiting the process of inflammation, angiogenesis, and metastasis in the tumor microenvironment. In addition, it has a preventive activity such as radio and/or chemosensitizer. These effects have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Despite bioavailability challenges, clinical trials with curcumin either alone or in combination as an anticancer agent have shown efficacy against several disease sites such as breast (Bayet-Robert et al, 2010), prostate (Mahammedi et al, 2016), pancreatic (Epelbaum et al, 2010;Kanai et al, 2013), colorectal (Sharma et al, 2004;Carroll et al, 2011;Irving et al, 2015;James et al, 2015), and hematological malignancies (Ghalaut et al, 2012). Latest information on various preclinical and clinical anticancer trials using curcumin is reviewed in Doello et al (2018). Recently, in patients with locally advanced or metastatic pancreatic cancer, curcumin Meriva ® (2,000 mg/day) in complementary to gemcitabine was found to increase the efficacy of gemcitabine without any treatment-related toxicity (Pastorelli et al, 2018).…”
Section: Phytochemicals Evaluated In Clinical Trialsmentioning
confidence: 99%
“…Despite bioavailability challenges, clinical trials with curcumin either alone or in combination as an anticancer agent have shown efficacy against several disease sites such as breast (Bayet-Robert et al, 2010), prostate (Mahammedi et al, 2016), pancreatic (Epelbaum et al, 2010;Kanai et al, 2013), colorectal (Sharma et al, 2004;Carroll et al, 2011;Irving et al, 2015;James et al, 2015), and hematological malignancies (Ghalaut et al, 2012). Latest information on various preclinical and clinical anticancer trials using curcumin is reviewed in Doello et al (2018). Recently, in patients with locally advanced or metastatic pancreatic cancer, curcumin Meriva ® (2,000 mg/day) in complementary to gemcitabine was found to increase the efficacy of gemcitabine without any treatment-related toxicity (Pastorelli et al, 2018).…”
Section: Phytochemicals Evaluated In Clinical Trialsmentioning
confidence: 99%
“…As described herein, the plant-derived MTAs, taccalonolides, persin, curcumin, combretastatins, noscapine, maytansine, chalcones, and quercetin, have exhibited improved anticancer properties when compared with the taxanes and vinca alkaloids. Of note, curcumin, combretastatins, noscapine, maytansine, and quercetin have already undergone clinical trials evaluating their efficacy against various cancers [43,46,63,87,93] (Table 2). Because targeted delivery of cytotoxic agents to cancer cells increases the percentage of drug molecules that reach the tumor, and thereby lowers the minimum effective dose and increases the maximum tolerated dose, maytansine ADCs may possibly have a promising future as a clinically succesful MTA among these compounds.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…With its multifaceted metabolic actions including anti-oxidant and anti-inflammatory activities, curcumin can selectively kill tumor cells (Ravindran et al, 2009;Gupta et al, 2013;Ghosh et al, 2015;Shanmugam et al, 2015;Hewlings and Kalman, 2017). Several clinical trials classify curcumin as a potential chemopreventive and chemotherapeutic agent (Hatcher et al, 2008;Doello et al, 2018). Curcumin has antioxidant effects via activation of the Nuclear factor erythroid 2-related factor 2 (Nrf2) expression (Balogun et al, 2003), and provides protection against oxidative damage induced by ferric nitrilotriacetate (Fe-NTA) (Iqbal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%